2013
DOI: 10.1002/hc.21132
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadducts of 1‐Alkyl‐1,2‐diphospholes with N‐Phenylmaleimide: Synthesis, Structure, Oxidation, and Thionation Reactions

Abstract: The [4+2] cycloaddition reaction of 1‐alkyl‐1,2‐diphospholes (1) with N‐phenylmaleimide proceeds at 25°С in toluene to give 1,7‐diphosphanorbornenes (2) as anti‐endo isomer only. Oxidation of 2 with air at room temperature or thionation with excess of sulfur at 80°С results in the formation of mixed valent PIII, PV 7‐oxo(thia)‐1,7‐diphosphanorbornenes (3, 4) in high yield. The polycyclic compounds 3 and 4 are air stable and have small sums of valence angles at the phosphorus atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The 1 H NMR spectra of the reaction mixtures show only two doublets for protons of the N -phenylmaleimide fragment in the range of 4.6–4.8 ppm. Based on our previous results [ 20 ], we can conclude that only an anti-endo- isomer was formed in each case.…”
Section: Resultssupporting
confidence: 51%
“…The 1 H NMR spectra of the reaction mixtures show only two doublets for protons of the N -phenylmaleimide fragment in the range of 4.6–4.8 ppm. Based on our previous results [ 20 ], we can conclude that only an anti-endo- isomer was formed in each case.…”
Section: Resultssupporting
confidence: 51%
“…It was previously shown that the bridging phosphorus atom P10 of 10-alkyl-7,8,9-triphenyl-1,10-diphosphatricyclo[5.2.1.0 2,6 ]-deca-8-ene-3,5-diones is involved in oxidation and sulfurization reactions [30]. Since the catalytic [3 + 2] cyclization is initiated by a nucleophilic attack of the phosphine at ethyl buta-2,3-dienoate (9) leading to a resonance-stabilized phosphonium dienolate, only the bridging phosphorus atom P10 should be involved here as well ( Table 2, right).…”
Section: Resultsmentioning
confidence: 99%
“…According to the X-ray data, only one of the possible isomers, specifically the syn-exo-isomer 3b was formed, although the products of [4+2] cycloaddition reactions of uncoordinated 1-alkyl-1,2-diphospholes have anti-endo-configuration. [41][42][43] The unit cell of 3b contains 8 independent molecules -4 of each enantiomer with…”
Section: Njc Papermentioning
confidence: 99%